A review of embodied energy (EM) analysis of Industrialised Building System (IBS) - Zaini, N.; Ibrahim, S.H.; Baharun, A.; Nawi, M.N.M. (Mohammed Premier University, 2016)
Sustainable design and construction have become global issues. Therefore, the reduction of carbon emission has become a main focus of environmental strategies around the world. In construction industries, the extraction of materials and the erection of buildings consume embodied energy and emit carbon dioxide (CO2) that caused negative impacts on the environment. Therefore, it is necessary to consider embodied energy and CO2 amongst other factors in selecting building materials used in building projects. The paper presents the on-going research which aims to developed life cycle assessment (LCA) methodology for estimation of embodied energy and carbon emission in a building that used Industrialised Building System (IBS) as an innovation construction process for the Malaysian construction industry. The methodology includes calculating environmental impacts of life cycle of building production in terms of embodied energy and carbon emission. For this study, the boundary of the studies and tools had been explained to assess embodied energy and carbon emission.